I am going! - Willems, Mo. (New York : Hyperion Books for Children, 2010)
Piggie ruins a perfectly good day by telling Gerald the elephant that she is going, sending him into a panic.
Booklist
Kirkus Starred
School Library Journal
Booklist, December 2009
Horn Book, March 2010
Kirkus Starred, December 2009
Keywords: Elephants -- Juvenile fiction; Friendship -- Juvenile fiction; Pigs -- Juvenile fiction; Elephants -- Fiction; Friendship -- Fiction; Humorous stories; Pigs -- Fiction; Elephants -- Fiction; Friendship -- Fiction; Humorous fiction; Pigs -- Fiction; Humorous fiction; Readers (Elementary).